ZITgoed : stoelen - verhalen. - Bernlef, Jan; Billiet, Daniel; Brecht, Bertolt; Burssens, Gaston; Jooris, Roland; Kindt, Floris; Valladares, Armando; Van Gogh, Ruben; van Steijn, Anneke; van den Berg, M.R. (Turnhout : De Warande, 2000)
Aalto, Alvar ; Asikainen, Teppo & Terho, Ilkka ; Bertoia, Harry ; Breuer, Marcel ; Castiglioni, Achille & Castiglioni, Pier Giacomo ; Chadwick & Stumpf ; Eames, Charles & Ray ; Jacobsen, Arne ; Kolhonen, Pasi & Suppanen, Ilkka ; van Lamers, Bas & Rooij, Bas ; Le Corbusier ; Mies van der Rohe, Ludwig ; Remy, Tejo ; Rietveld, Gerrit ; Segers, Karen ; Wegner, Hans J.
Nederlands
ZITgoed, de Warande, Turnhout, van 23 december 2000 tot en met 15 april 2001
kunstcatalogus